IMPLEMENTATION OF KEEP ON LEARNING STRATEGY TO IMPROVE STUDENT LEARNING OUTCOMES IN SCIENCE SUBJECTS CLASS IV STATE ELEMENTARY SCHOOL 142 BENGKULU UTARA - Watini; Azmi , Ulil (Journal of Higher Education and Academic Advancement, 2024)
Objective: This study examines the implementation of the "Keep on Learning" strategy to enhance science learning outcomes for Grade IV students at Elementary School 142 North Bengkulu. It aims to identify effective practices and address obstacles hindering its success. Method: A qualitative research approach was employed, utilizing field research with primary and secondary data sources. Data collection included interviews, observations, and document analysis to explore the strategy's implementation and its challenges. Results: The study found that the strategy effectively improved student engagement and learning outcomes through project-based activities, experiments, technology integration, group discussions, independent assignments with feedback, and supplementary resources like videos and articles. However, several challenges were identified, including limited access to technology, insufficient parental support, and inadequate teacher preparedness. Novelty: This research highlights the critical role of continuous learning strategies tailored to elementary-level science education and provides actionable solutions, such as targeted teacher training, enhanced infrastructure, and increased community involvement, to overcome implementation barriers and optimize student outcomes.